2015
DOI: 10.1109/jstars.2014.2379438
|View full text |Cite
|
Sign up to set email alerts
|

A Simple RVoG Test for PolInSAR Data

Abstract: Abstract-In this paper, we present a simple algorithm for assessing the validity of the RVoG model for PolInSAR-based inversion techniques. This approach makes use of two important features characterizing a homogeneous random volume over a ground surface, i.e., the independence on polarization states of wave propagation through the volume and the structure of the polarimetric interferometric coherency matrix. These two features have led to two different methods proposed in the literature for retrieving the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…At P band, precious works have shown that the volume scattering contribution is polarization-dependent since the orientation effect has been observed over forests [14,15,23]. As a result, this cannot meet the RVoG assumption and may induce biases of ground phase estimated by the three-stage inversion procedure [23].…”
Section: Coherence Locus Of Gvbmentioning
confidence: 99%
See 1 more Smart Citation
“…At P band, precious works have shown that the volume scattering contribution is polarization-dependent since the orientation effect has been observed over forests [14,15,23]. As a result, this cannot meet the RVoG assumption and may induce biases of ground phase estimated by the three-stage inversion procedure [23].…”
Section: Coherence Locus Of Gvbmentioning
confidence: 99%
“…As a result, this cannot meet the RVoG assumption and may induce biases of ground phase estimated by the three-stage inversion procedure [23]. Nonetheless, the biases may be small and acceptable forest height results have been successfully extracted using the RVoG assumption at P band over the tropical and pine forests [24][25][26][27].…”
Section: Coherence Locus Of Gvbmentioning
confidence: 99%
“…On account of the significant penetration of P-band polarimetric interferometric synthetic aperture radar (Pol-InSAR) systems, all polarimetric channels contain a non-ignorable ground contribution [1][2][3][4][5], generally leading to an underestimation of forest height in view of the Random Volume over Ground (RVoG) model [3,6]. So far, the RVoG model depicting the forest vertical backscatter profile with an exponential function has been widely taken advantage of in forest height estimation [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Moroever, when referring to temporal decorrelation [21][22][23][24][25], canopy filling [12,26] and terrain fluctuations [6,[27][28][29][30][31][32], some modified models were proposed to complement the RVoG model.…”
Section: Introductionmentioning
confidence: 99%
“…The complex interferometric coherence of the observed PolInSAR data has been related to the vertical distribution of the vegetation scattering [10][11][12]. In a number of PolInSAR campaigns, the random volume over ground (RVoG) model [6,10] has been used to extract vegetation height from the complex interferometric coherence [15][16][17]. The RVoG model is a physical PolInSAR model that integrates the complex coherence and the biophysical parameters.…”
Section: Introductionmentioning
confidence: 99%